Structural Characterization and Anti-breast Cancer Activity in vitro of a Novel Polysaccharide From Cymbopogon citratus - Chen, Yi; Qiao, Saifeng; Liu, Huiping; Xing, Huizhen; Chen, Pei (Frontiers in Nutrition, 2022)
Cymbopogon citratus is an important functional food, widely used for flavoring in Africa and South America. In this study, a novel high-molecular-weight polysaccharide (CCP) from Cymbopogon citratus was extracted, and its structural characteristics and anti-breast cancer activity in vitro were investigated. CCP contained both α and β configurations and mainly composed of galactose (36.89%), arabinose (23.97%), glucose (18.35%) and rhamnose (9.36%) with an average molecular weight of 1.98×106 Da. The main glycosyl residues of CCP detected by methylation analysis were 1,3,6-linked Galp, 1,3-linked Glcp, 1,5-linked Araf, T-Araf, and T-Rhap. In vitro experiments suggested that CCP significantly inhibited the proliferation of MDA-MB-231 cells, decreased the expressions of cyclin D1 and CDK4 and stocked cells at G0/G1 phase. Meanwhile, the typical morphological features of apoptotic cells were also observed. Combining with the consequences of Annexin V-FITC/PI staining, Hoechst 33258 staining and western blot analysis, CCP induced apoptosis of MDA-MB-231 cells by triggering the Fas/FasL-mediated death receptor pathway. Overall, these results provide a theoretical basis for the application of Cymbopogon citratus polysaccharide as a potential anti-breast cancer agent in functional food and medicine.